CYP19A1 fine-mapping and Mendelian randomization: estradiol is causal for endometrial cancer. Issue 2 (16th November 2015) - Thompson, Deborah J; O'Mara, Tracy A; Glubb, Dylan M; Painter, Jodie N; Cheng, Timothy; Folkerd, Elizabeth; Doody, Deborah; Dennis, Joe; Webb, Penelope M; ,; Gorman, Maggie; Martin, Lynn; et al.
Abstract : Candidate gene studies have reported CYP19A1 variants to be associated with endometrial cancer and with estradiol (E2 ) concentrations. We analyzed 2937 single nucleotide polymorphisms (SNPs) in 6608 endometrial cancer cases and 37 925 controls and report the first genome wide-significant association between endometrial cancer and a CYP19A1 SNP (rs727479 in intron 2, P =4.8×10 −11 ). SNP rs727479 was also among those most strongly associated with circulating E2 concentrations in 2767 post-menopausal controls ( P =7.4×10 −8 ). The observed endometrial cancer odds ratio per rs727479 A-allele (1.15, CI=1.11–1.21) is compatible with that predicted by the observed effect on E2 concentrations (1.09, CI=1.03–1.21), consistent with the hypothesis that endometrial cancer risk is driven by E2 . From 28 candidate-causal SNPs, 12 co-located with three putative gene-regulatory elements and their risk alleles associated with higher CYP19A1 expression in bioinformatical analyses. For both phenotypes, the associations with rs727479 were stronger among women with a higher BMI ( P interaction =0.034 and 0.066 respectively), suggesting a biologically plausible gene-environment interaction.